Thiolato-bridged arene ruthenium complexes as anticancer agents - Stíbal, David (My University, 2015)
Cancer is a major cause of morbidity and mortality in today’s world, affecting populations in all countries and all regions. Although no drug or treatment able to cure cancer in all of its forms and variations was found so far, the clinical advancements of 20th and 21st century provided a number of effective drugs for specific types of cancers and had a significant effect on the survival and the quality of life of patients. One of these drugs, the platinum-based complex cisplatin, achieved almost 100% cure rate of testicular cancer, not only saving lives of thousands of patients every year but also overturning a paradigm of medicinal chemistry – it was the first metal-based anticancer drug used in the clinic. The success of cisplatin encouraged the search for new metal-based anticancer agents, which soon expanded to other metals, such as ruthenium. During the last three decades, numerous ruthenium-based compounds with interesting anticancer properties were prepared and thoroughly investigated, two of which (NAMI-A and KP1019) were ultimately introduced into clinical trials, showing the potential of ruthenium complexes in cancer therapy.
The goal of the presented thesis was to investigate the properties of dinuclear arene ruthenium thiolato-bridged complexes and to establish their potential as anticancer drugs. In the first part of the thesis, several monothiolato, dithiolato and trithiolato complexes were synthesized and evaluated for their stability and reactivity with biological substrates. The results were correlated with the in vitro anticancer activity of the three types of complexes and showed the most stable trithiolato complexes to be the most active against ovarian cancer cell lines. Subsequently, the most active trithiolato derivative, diruthenium-1, was thoroughly investigated in vitro and in vivo to establish the mode of action of this complex, showing its promising ability to influence the tumor growth and to prolong the survival of tumor-bearing mice.
In the second part of this thesis, three series of conjugates of the mixed trithiolato complexes were synthesized to demonstrate the potential of the coupling of dinuclear arene ruthenium complexes with biologically active organic molecules. Thus, the thiolato-bridged complexes were coupled with propargyl bromide, the resulting conjugates being available for the 1,3-Huisgen addition with tumor targeting compounds. Conjugates with ibuprofen were synthesized to investigate the effect of the antiinflamatory agent on the activity and selectivity of the resulting complexes towards cancer cells. Finally, conjugates of dinuclear trithiolato arene ruthenium complexes with alkylating agent chlorambucil were synthesized to show the effect of the two different modes of action of the conjugates on their activity in vitro and in vivo.
These results demonstrate the potential of the dinuclear thiolato-bridged arene ruthenium complexes as a versatile platform for the synthesis of anticancer agents with variable biological properties and modes of action.
Thèse de doctorat : Université de Neuchâtel, 2015
Keywords: Complexes organométalliques; complexes dinucléaires arène ruthénium; ligands thiolato; cytotoxicité; activité anticancéreuse; Organometallic complexes; dinuclear arene ruthenium complexes; thiolato ligands; cytotoxicity; anticancer activity